The consumer awareness through direct response on media comercial (PPZ – MAIWP) / Nor Fitrina Abdul Rohani - Abdul Rohani, Nor Fitrina (Faculty of Business and Management, 2009)
Media is important to all countries in using in marketing strategic planning. In this project will focus consumer awareness on media commercial through radio, newspaper, magazine, billboard and brochure of direct response in zakat, Kuala Lumpur. A problem is the collection can show with the graft on every year to knowing the potential to gain more profit. Actually, at1997 until 1999 the collection has given a bad result on the years. So, this method to have assist the problem with use the direct response on media commercial to create awareness and educate a public person to become customer on the important of pay a zakat for all Muslim. For this study, 100 questionnaires will be distributed equally among customers and members of PPZ-MAIWP. For this research, the researcher uses cluster sampling from probability sampling to distribute the questionnaires to the potential respondents at PPZ-MAIWP and that will can use the suggestion method that should be use to complete this study are reliability test, correlation, coefficient and regression backward. In order to test the validity and reliability of the data used for this study. In this final report I want to improve and build the weakness on promotion zakat on media commercials towards radio, magazine, newspaper, brochure and billboard. The finding the Cronbach’s Alpha for the study is 0.852. In general, reliabilities ranged from 0.8 – 0.89 are considered very good. Thus, the internal consistency reliability of the measures used in this study can be considered consistent and stable. The “N”, Which is 28 items, represent the number of items that is data related to research objectives. This can assist their problem how gain more collection on zakat by every year. Besides that, the researcher also came out with some recommendation in order to make the consumer awareness on media commercials of PPZ-MAIWP become more effective and create interest of Muslim to pay zakat.